THE INTERRELATIONSHIP BETWEEN MSME GROWTH, INVESTMENT, AND EMPLOYMENT: A STATISTICAL ANALYSIS IN ASSAM, INDIA - Muchahary, Phung Roje; Brahmachary, Pradip (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Micro, Small, and Medium Enterprises (MSMEs) sector is a vital pillar of the Indian economy, significantly contributing to gross domestic product (GDP), industrial output, employment, and exports. This study explores MSME growth and its impact on employment generation in Assam from 2010 to 2020, using secondary data from MSME annual reports, the Assam Statistical Handbook, and other sources. The analysis examines trends in MSMEs, jobs, and investments, employing forecasting, regression analysis, and confidence intervals to assess growth patterns. Results reveal fluctuating trends in MSMEs, employment, and investments, with notable peaks in 2020-2021. The compound annual growth rate (CAGR) for MSMEs and jobs was 16.23% and 16.39%, respectively, indicating strong growth despite occasional declines. Regression analysis shows a significant positive correlation between MSMEs and job creation, while investment had a lesser impact. The findings emphasize MSMEs as key drivers of employment in Assam, offering valuable insights for policymakers.